Aposeris foetida (L.) Cass. ex Less., confirmed as a host-plant of Trioza foersteri Meyer-Dür, 1871 (Hemiptera: Psylloidea: Triozidae) - Seljak, Gabrijel (Acta entomologica slovenica (Ljubljana), 2018)
In the past, pit-galls on leaves of Aposeris foetida (L.) Cass. ex Less. (Asteraceae) have been attributed to Trioza dispar Löw, 1876 (Homoptera: Psylloidea: Triozidae), although there were some hesitations regarding this host association. Rearing of immatures to the adult stage in controlled conditions showed unambiguously that Trioza foersteri Meyer-Dür, 1871 causes these pit-galls and A. foetida is its true host-plant. Hence, all earlier records of T. dispar referring to A. foetida should be reassociated with T. foersteri. In Slovenia, this species is widely distributed but uncommon and A. foetida has been the only recorded host-plant so far, since there have been no records on the occurrence of pit-galls and immatures on its other known host-plants, Lactuca muralis and Prenanthes purpurea. During the rearing assay a considerable number of specimens of the parasitoid wasp Tamarixia upis (Walker, 1839) (Hymenoptera: Chalcidoidea: Eulophidae) emerged from parasitized immatures. Trioza foersteri is reported as a new host of this parasitoid wasp here. A complementary description of the fifth instar nymph of T. foersteri is provided. Several stages are documented with a series of photographs.
Keywords: Aposeris foetida; Astraceae; biology; boljšice; galls; gostiteljske rastline; Hemiptera; host-plants; immature morphology; jumping plant-lices; parasitoids; Psylloidea; Slovenia; Slovenija; šiške; Trioza foersteri; Triozidae; zajedalci